Proc. 27th Annual Conference of the International Group for Lean Construction (IGLC) 2019
DOI: 10.24928/2019/0247
|View full text |Cite
|
Sign up to set email alerts
|

The Beauty of a Phase-Overlapping Last Planner System® With Incorporated Takt

Abstract: The purpose of methods and tools is to serve the project team and add value within the project delivery. Therefore, the implemented production system should support the interaction of the project team, enabling team members to develop a common understanding, and to reach the required quality and production performance when carrying out their daily activities. This research concludes that the Last Planner ® System (LPS) aligns to the Toyota Production System (TPS) and its recognized management theory, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…After the handover of the building, those team members were successively spread out to other projects in Germany and Austria in January 2019. At the same time, 21 interviews were conducted amongst others regarding the implemented production system, decision-making, and collaboration about the BMW Freimann project (Schöttle and Nesensohn 2019). These interviews showed the importance of a production system that is based on product request and the project team's needs, and serves as a reference point to discover the motivation of the selected group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the handover of the building, those team members were successively spread out to other projects in Germany and Austria in January 2019. At the same time, 21 interviews were conducted amongst others regarding the implemented production system, decision-making, and collaboration about the BMW Freimann project (Schöttle and Nesensohn 2019). These interviews showed the importance of a production system that is based on product request and the project team's needs, and serves as a reference point to discover the motivation of the selected group.…”
Section: Methodsmentioning
confidence: 99%
“…During the construction phase a takt was integrated into the LPS for repeatable areas. Lean and the LPS were new to all project participants as well as to their organizations (Schöttle and Nesensohn 2019). Based on interviews, observations, and workshops, Schöttle and Nesensohn (2019) found that a phase-overlapping production system such as the LPS can help to create a collaborative environment.…”
Section: Data Analysis Reference and Current Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…From a social standpoint, LPS focuses on controlling the production system by managing conversations, relationships, and commitments among participants (González et al 2015b). Essentially, it facilitates elaborating not only practical plans and reliable workflows but also building project teams aimed at increasing the accountability of its members (González et al 2015b;Schöttle and Nesensohn 2019). Social dynamics refers to understanding the relationship between individual-level interactions and group-level behaviours by exploring responses resulting from interactions among internal individuals (González et al 2015b).…”
Section: Socio-technical Dynamics In Lps Implementationmentioning
confidence: 99%
“…The benefits of Last Planner System® (LPS) have been well-reported, and its popularity has grown in time, but a holistic implementation is still difficult in many organisations (Fernandez-Solis et al 2013;Perez and Ghosh, 2018). Other studies on LPS have realised that this challenge originates from the lack of capacity of the project team and organisation to adapt processes and behaviours to both the social and technical nature of LPS (González et al 2015b;Perez and Ghosh 2018;Schöttle and Nesensohn 2019). These studies support the notion that the limitations in understanding that LPS is a lean methodology that encompasses not only technical expertise and knowledge associated with planning and control but also it engenders changes in the social dynamics of construction organisations.…”
Section: Introductionmentioning
confidence: 99%